Neck and back pain: Differences between patients treated in primary and specialist health care - Mari Kristine Tyrdal; Marit B. Veierød; Cecilie Røe; Bård Natvig; Astrid Klopstad Wahl; Hilde Stendal Robinson (Medical Journals Sweden, 2022)
Objective: To describe and compare patients with neck and back pain treated by physiotherapists in primary healthcare (PHC) and in departments for physical medicine and rehabilitation in specialist healthcare (SHC) in Norway. Design: Cross-sectional study using data from the FYSIOPRIM database in PHC and the Norwegian Neck and Back Registry in SHC. Neck and back pain patients in the period 2014-18 aged ≥ 18 years were included. Demographics, lifestyle and clinical factors were investigated. Results: A total of 8,125 patients were included: 584 in PHC and 7,541 in SHC. Mean age was 47.1 and 45.5 years, respectively, with more females in PHC (72% vs 56%). Low levels of education and physical activity, high workload and receiving social benefits were associated with treatment in SHC. Treatment in SHC was most common from 3 to 12 months' pain duration. Higher pain intensity and lower health-related quality of life were found in patients treated in SHC, no differences were found for psychological distress. Conclusion: This is the first study comparing register data in patients with neck and back pain treated in PHC and SHC. Differences were found in pain and health-related quality of life, but levels of psychological distress were similar between patients treated in PHC and those treated in SHC.